Comparative metabolomics analysis reveals dynamic changes in carbohydrate profiles of corms during the “relay growth” of konjac (Amorphophallus muelleri) - Qi, Ying; Gao, Penghua; Yang, Shaowu; Li, Lifang; Ke, Yanguo; Wei, Huanyu; Huang, Feiyan; Yu, Lei (Frontiers in Plant Science, 2023)
The type and content of carbohydrates in konjac corms are an essential factors in determining the quality of konjac; however, the pattern of carbohydrate changes and the mechanism regulating the development of mother and daughter corms in the "relay growth" process of Amorphophallus muelleri remain unclear. This study aimed to investigate changes in corm carbohydrates during the growth cycle of A. muelleri and to compare the carbohydrate composition and the expression of related genes between mother and daughter corms. Integrated metabolome and RNA-seq analyses identified 37 differential metabolites as well as 8074 genes that were differentially expressed between mother and daughter corms, the majority of which were involved in starch and sucrose metabolism. More than 80% of the differential metabolites, including sucrose and starch, tended to accumulate in the mother corms; however, konjac glucomannan (KGM), as one of the most important carbohydrates and its major component of the corm, accumulated in higher amounts in the daughter corms. In addition, the expression of invertase and alpha-amylase that promote the breakdown of sucrose and starch was 351.78-and 15.63-fold higher, respectively, in the daughter corm, whereas that of the starch synthesis gene AkWAXY was only 0.096 times as high as in the mother corms.Furthermore, the level of cellulose synthase-like protein G, which promotes KGM synthesis, was 3.85 times higher in daughter corms compared to mother corms. Thus, we inferred that the daughter and mother corms had two distinct carbohydrate utilization strategies. This study provides insights into temporal changes in carbohydrates during the growth cycle of A. muelleri.